THE ROLE OF SOFTWARE IN A CASHLESS ECONOMY (CASE STUDY NIGERIA) - Ebimobowei, Sese Tuperekiye; Enebraye Peter, Zoukemefa; Pual, Yerikema (International Journal of Research -GRANTHAALAYAH, 2018)
In the world today most country’s economy is gradually going cashless and Nigeria is no exception. In other for this to be achieved the use of computers and computerized networks and its software comes greatly into play. In an attempt to make the country’s economy cashless driven, we will discover that software plays a prominent role and can only be unveiled when we take a close study of how some of these payment mechanisms functions. Such mechanisms include POS TERMINALS, smart mobile phones and computers (laptop/desk top). There are basically two categories of software are installed on each of these devices; they include an operating system and application software. Also this paper went the extra mile of explaining what cashless economy is, the aim of establishing the policy in Nigeria and the benefits.